Ang lalake sa parola - Del Rosario, Vincent; ALtarejos, Joselito (Viva Video, 2007)
"After meeting Mateo, a lighthouse caretaker, Jerome, a gay man from the city finds himself deeply attracted to this simple yet seductive man. Soon, Mateo finds himself entering a subtle homoerotic journey with his newfound friend, while Suzet, Mateo's girlfriend, continues to struggle for his love and attention. Will Mateo bravely cross the thin line between being straight and being gay in the midst of his conservative rural community? This story is a search for oneself as seen through the lens of rural homosexuality, legends and fairies and the lies that men create to escape the bitter realities of this world."